Hepatitis C virus infection among patients on hemodialysis: A report from a single center in Iran - Nemati Eghlim (Saudi Journal of Kidney Diseases and Transplantation, 2009)
The aim of this study is to evaluate the incidence of hepatitis C virus (HCV) infec-tion among the hemodialysis (HD) patients at the Nephrology and Urology Research Center, Tehran, Iran, and identify the potential risk factors. A total of 112 patients on HD in our two dia-lysis units were studied. The mean duration of follow-up was 27 ± 27 months (range, 6-132). All study subjects were HCV-negative at entry to the study and were tested for anti-HCV antibody by ELISA II every six months thereafter. Positive samples were re-examined by RT/PCR for confir-mation. Factors that might be implicated in HCV transmission were evaluated. Six patients (5.3%) were labeled as HCV infected, at the end of the follow-up period. Thus, the incidence of HCV infection in our dialysis units was 1.8 per 100 person years. A total of 64.5% of the study popu-lation had previous history of blood transfusion(s) and 8% had undergone prior transplantation. Univariate analysis showed a significant relationship between number of blood transfusions and duration on dialysis and HCV infection. Multivariate analysis revealed that only duration on HD was significantly associated with HCV positivity (OR: 1.03, p=0.008). Our study further suggests that nosocomial transmission plays a major role in HCV transmission among patients on HD. Meticulous practice of preventive measures is essential to eradicate the spread of HCV in HD units.